Assessment of the effectiveness of the innovative potential of industrial enterprises (Economics and region, 2025)
In modern conditions, the successful operation and sustainable development of an industrial enterprise requires comprehensive improvement of key performance indicators, the formation and application of innovative management methods, the organization of innovative production processes and technologies, and the intensification of the use of the accumulated innovative potential and methods of its development for the production of high-quality and high-tech products in demand in the national and world markets. Modeling of production processes and resources is currently one of the main tools of enterprise management in organizing the management of complex production and economic systems. To implement innovative activities, industrial enterprises need the innovative potential formed and accumulated, as well as the conditions for its successful implementation. Innovative potential is a parameter that allows assessing the capabilities and skills of the enterprise management to implement real innovative activities and form a strategy for the innovative development of an industrial enterprise. Currently, the issue of economic assessment of the level of innovative potential and its resources in industrial enterprises as a whole is very relevant. According to the authors, when determining the level of the accumulated innovative potential of an enterprise, it is necessary to use diagnostics as a method of analyzing the existing incomplete characteristics and indicators of the activity of the subjects of the economic-production system. Taking all this into account, the article presents the sequence of stages of formation, development and implementation of innovative potential in the implementation of an innovation project, analyzes the level of the accumulated innovative potential of the enterprise by diagnostic types, and proposes a diagnostic method for the level of the accumulated innovative potential of the enterprise based on the adequacy of the main components of the innovative potential, the ability of the enterprise to carry out innovative activities in the present and future, and the parameters of its capabilities, and expert assessment.
Keywords: industrial enterprises; modeling; innovative potential; assessment; index; efficiency; diagnostics; innovation project